Optical absorption spectra of Xene and Xane (X = silic, german, stan). (6th July 2021) - Nguyen-Truong, Hieu T; Van On, Vo; Lin, Ming-Fa
Abstract: We study optical absorption spectra of Xene and Xane (X = silic, german, stan). The results show that the optical absorption spectra of Xenes are dominated by a sharp peak near the origin due to direct interband transitions near the K point of the Brillouin zone. Meanwhile, the optical absorption spectra of Xanes are characterized by an excitonic peak. The Xenes are zero-gap materials with a Dirac cone at the K point, whereas Xanes are semiconductors with sizable band gaps. The quasiparticle band gaps of silicane, germanane, and stanane are 3.60, 2.21, and 1.35 eV, respectively; their exciton binding energies are 0.40, 0.33, and 0.20 eV, respectively.